Role of Probiotic, Prebiotic and Synbiotic on Growth Performance and Biometric Development of Jaffarabadi Buffalo Calves - A Pata, Bharat; R Gadariya, Mahesh; V Gamit, Viral; H Savsani, Harish; D Odedra, Mulraj; P Sabapara, Ghanshyam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was aimed to investigate the effects of probiotic, prebiotic and synbiotic supplementation on growth performance  and biometric parameters in Jaffarabadi buffalo calves. A total of 24 neonatal calves were divided into four equal groups: Control (C),  Probiotic (T1), Prebiotic (T2) and Synbiotic (T3), each consisting of six calves. The calves were fed a restricted suckling diet, supplemented  with basal feed and each group received specific additives: T1 (probiotic), T2 (prebiotic) and T3 (synbiotic). The experiment was conducted  for 175 days, from 8 to 182 days of age. Results showed that calves in the T1, T2 and T3 groups exhibited significantly higher growth rates  compared to the control group (p
Keywords: ADG; Biometric measurements; Growth performance; Jaffarabadi buffalo calves; Prebiotics; Probiotics